Hypolipidemic mechanism of Pleurotus eryngii polysaccharides in high-fat diet-induced obese mice based on metabolomics - Zhao, Yuanyuan; Zhang, Zhen; Wang, Li; Li, Wen; Du, Jianming; Zhang, Shengxiang; Chen, Xuefeng (Frontiers in Nutrition, 2023)
Objective: In this study, the structure of Pleurotus eryngii polysaccharides (PEPs) was characterized, and the mechanism of PEP on obesity and hyperlipidemia induced by high-fat diet was evaluated by metabonomic analysis. Methods: The structure of PEPs were characterized by monosaccharide composition, Fourier transform infrared spectroscopy and thermogravimetry. In animal experiments, H&E staining was used to observe the morphological difference of epididymal adipose tissue of mice in each group. Ultrahigh performance liquid chromatography (UHPLC)-(QE) HFX -mass spectrometry (MS) was used to analyze the difference of metabolites in serum of mice in each group and the related metabolic pathways. Results: The PEPs contained nine monosaccharides: 1.05% fucose, 0.30% arabinose, 17.94% galactose, 53.49% glucose, 1.24% xylose, 23.32% mannose, 1.30% ribose, 0.21%galacturonic acid, and 1.17% glucuronic acid. The PEPs began to degrade at 251 °C (T0), while the maximum thermal degradation rate temperature (Tm) appeared at 300 °C. The results histopathological observation demonstrated that the PEPs had signifificant hypolipidemic activities. After PEPs intervention, the metabolic profifile of mice changed significantly. A total of 29 different metabolites were selected as adjunctive therapy to PEPs, for treatment of obesity and hyperlipidemia-related complications caused by a high-fat diet. These metabolites include amino acids, unsaturated fatty acids, choline, glycerol phospholipids, and other endogenous compounds, which can prevent and treat obesity and hyperlipidemia caused by a high-fat diet by regulating amino acid metabolism, fatty acid metabolism, and changes in metabolic pathways such as that involved in the citric cycle (TCA cycle). Conclusions: The presented results indicate that PEPs treatment can alleviate the obesity and hyperlipidemia caused by a high-fat diet and, thus, may be used as a functional food adjuvant, providing a theoretical basis and technical guidance for the prevention and treatment of high-fat diet-induced obesity and hyperlipidemia. Keywords: Pleurotus eryngii polysaccharides; structural characterization; obesity; metabolic pathways; Metabolic differences